A Systematic Query Search on the Interplay between Remote Working and COVID-19: Data-driven Analysis - Mthombeni, Thoko; Matli, Walter (Procedia computer science, 2024)
Remote working has become increasingly popular in recent years, with the COVID-19 pandemic further accelerating its adoption worldwide. This paper aims to analyse publication data from the Scopus database and associated journals to investigate the relationship between remote working and the COVID-19 pandemic. By performing a query search using the keywords "remote working" and "COVID-19," a comprehensive analysis of peer-reviewed journal articles published within a specific timeframe was conducted to ensure relevance and currency of information. The findings demonstrate a substantial increase in research articles focusing on remote working and COVID-19, spanning various disciplines. The analysis of the Scopus database and associated journal publications enables researchers to identify gaps in the existing literature on the subject. By examining the discipline, subject area, and article type, researchers can pinpoint areas that require further contributions. This analysis provides valuable insights for future research endeavours, guiding researchers towards unexplored and saturated aspects of remote working and its implications during the pandemic.